Teachers Professional Development And Students' Academic Achievement In Public Senior Secondary School In Niger State, Nigeria - Olaifa, Adeseko Sunday; Ciroma, Usman Abdul; Olaifa, Ebunlomo Oreoluwa; Onikoyi, Olawale Abayomi; Shittu, Adesina Afeez (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study investigated teacher's professional development and students' academic achievement in public senior secondary schools in Niger State, Nigeria. The descriptive survey of the correlational type was adopted for the study. The population of this study comprised 7,825 Public Senior Secondary School Teachers. A sample of 367 teachers was selected using purposive and simple random sampling techniques. A researcher-designed instrument titled